Peran Dinas Perlindungan Perempuan dan Anak dalam Pemenuhan Hak-Hak Anak Korban Tindak Pidana Kekerasan Seksual: Studi pada Wilayah Hukum Kabupaten Mesuji - M. Ariessandy Agustin (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
Efforts to protect children who are victims of sexual violence crimes in Mesuji Regency have been carried out through the establishment of the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA). However, in practice, cases of sexual violence against children continue to occur. This study aims to analyze the role of the UPTD PPA of Mesuji Regency in fulfilling the rights of child victims of sexual violence crimes and to identify the factors that hinder the implementation of this role. This research employs normative juridical and empirical approaches. Data were collected through literature review and field studies, with informants consisting of the Head of the Mesuji Regency Office for Women’s Empowerment and Child Protection, the Head of the UPTD PPA of Mesuji Regency, and a lecturer in criminal law from the Faculty of Law, University of Lampung. Data analysis was conducted qualitatively. The results show that, normatively, the role of the UPTD PPA of Mesuji Regency has been implemented based on the prevailing laws and regulations, including the Child Protection Law, the Law on Sexual Violence Crimes, and regulations concerning the UPTD PPA. Factually, the UPTD PPA carries out preventive, handling, and recovery efforts through legal, medical, and psychological protection for child victims. However, the implementation of this role has not been optimal due to several inhibiting factors, namely limitations in human resources, inadequate facilities and infrastructure, low community participation and awareness, and cultural factors characterized by individualism. This study recommends optimizing the performance of the UPTD PPA through improvements in human resources, facilities and infrastructure, and strengthening community involvement in child protection.